Оцінка ефективності управління збутовою діяльністю туристичних підприємств - Музичка, Єлизавета Олександрівна (My University, 2013)
У статті запропоновано методику оцінки ефективності управління збутовою діяльністю туристичних підприємств, що представлена моделлю оцінки ефективності. Описана модель включає напрями оцінки зовнішньої і внутрішньої ефективності збутової діяльності та її складові – оцінку ефективності каналу збуту, оцінку ефективності збуту з точки зору продавця і покупця туристичних послуг. Основними критеріями оцінки ефективності збутової діяльності є збільшення кількості клієнтів (споживачів), обсягу реалізованих послуг та регіональних представництв. Індикаторами оцінки ефективності управління збутовою діяльністю є підвищення рівня доходності підприємств, зростання ринкової частки на регіональному (обласному) і загальнодержавному рівнях, а показниками – коефіцієнт концентрації ринку, індекс Розенблюта, маркетингова привабливість, інтенсивність конкуренції, а також темпи приросту ринкової частки, збутових витрат та ін. Застосування напрацьованої автором методики і системи показників оцінки ефективності дасть змогу підприємствам обрати серед альтернативних шляхів управління збутом найбільш результативний. Sales management of tourism enterprises is provided by the functions of planning, organization, motivation; sales control must be carried out with a maximum efficiency. Methodology to estimate efficiency of sales management of tourism enterprises is proposed in the research paper; and it is represented by efficiency estimate model which includes estimation of internal and external efficiency of sales and its components – estimated of efficiency of a distribution channel, efficient sales in terms of the seller and buyer of tourist services. The major criteria for estimating the efficiency of sales are increasing of the number of customers (consumers), the volume of services sold and the development of regional offices. Indicators for efficiency estimating of sales management are increase of enterprise’s profitability, increase of market share at regional and national level. Efficiency indexes of sales management are those of determining the market share of touristic enterprises (national market share, marketing attractiveness, competition rate, market concentration index, Rosenbluth Index) and indicators of tourism enterprises marketing expenditures effectiveness determining (market share growth, market increase rate, marketing costs increase rate and other). Application of the author’s worked out methods and evaluation indicators allow businesses to choose the most efficient type of sales management among alternative ones.
Keywords: управління збутом; ефективність; економічність; результативність; модель оцінки; sales management; effectiveness; efficiency; cost effectiveness; evaluation model; кафедра туристичного та готельного бізнесу